Effects of a parent advocacy intervention on service access for transition‐aged autistic youth: a multisite randomized controlled trial - Taylor, Julie Lounds; DaWalt, Leann Smith; Burke, Meghan M.; Xu, Meng; Slaughter, James C. (Journal of child psychology and psychiatry, 2025)
Autistic youth in the United States face many challenges accessing services as they transition to adulthood. Improving parents' ability to advocate for services is a promising way to improve service access. The current study tested whether participation in an intervention to improve parents' ability to advocate for adult services (called Advocating for Supports to Improve Service Transitions or ASSIST) led to increased service access for their transition-aged autistic youth. Using a multisite, single-blind parallel-group design, we randomized 185 parents of transition-aged autistic youth to either a treatment condition that received the ASSIST intervention, or a control condition that received comprehensive written information about adult services. Primary outcomes for this report - number of government programs that fund services and direct services received by the youth - were collected via parental interview at baseline, six, and 12 months after intervention. Primary analyses found no significant treatment effects on service access. Subgroup analyses, however, detected treatment effects for families of youth who had exited high school prior to their families taking ASSIST. Among those families, youth from the treatment group were receiving more government programs that fund services at 6 months after intervention compared with youth from the control group. We cannot conclude from our findings that ASSIST improved access to services, though there was some evidence to suggest increased access to government programs that fund services for families of autistic youth who had exited high school. Future research should investigate which families can translate written information about adult services (i.e. the control condition) into improved service access, and which families need more individualized support beyond a group-based class to see improvements in service access.